Tatalaksana Jalan Napas - Putri Monganisa Alwy; Abrar Abrar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
To become proficient in airway management, a physician must have a thorough understanding of the relevant anatomy, physiology, and pathology of the airway. Knowledge of the tools and techniques used in airway management is essential. In addition, understanding the indications, contraindications, and potential complications of endotracheal intubation is also crucial. Ensuring proper endotracheal tube (ETT) placement remains essential. Clinicians also need to recognize the differences between the airways in adults, children, and neonates, and master strategies for managing difficult airways, as part of the effort to achieve safe and effective airway control.